Simultaneous Determination of 9 Biogenic Amines in Larimichthys polyactis by UHPLC-MS/MS - Zhenling LUO; Haibo GAO; Ting YANG; Yu FU (Shipin gongye ke-ji, 2023)
To rapidly determine 9 biogenic amines including spermine, spermidine, putrescine, cadaverine, histamine, tryptamine, octopamine, tyramine and β-phenethylamine in aquatic products, the ultra high-performance liquid chromatography-tandem mass spectrometry method was established with Larimichthys polyactis using as matrix sample, and mobile phase and extract solvents were optimized. Matrix sample was extracted by 0.1% trichloroacetic acid (TCA) in duplicate, the supernatant was combined and filtered by 0.22 μm PTFE filters, and separated by HSS T3 column in 4 min. The mobile phase A was acetonitrile containing 0.1% formic acid, while mobile phase B was 10 mmol/L ammonium formate containing 0.2% formic acid. Nine biogenic amines were divided into three groups based on their different response intensity, with a concentration range of 1 to 40 ng/mL (tyramine and β-phenethylamine), 5 to 200 ng/mL (putrescine, cadaverine, histamine, tryptamine and octopamine), and 25 to 1000 ng/mL (spermine and spermidine). Their method quantification limits (LOQs) were 0.01, 0.05 and 0.25 mg/kg, respectively. The recovery rate of low, medium and high concentrations was 81.7%~111.2%, 80.0%~110.3% and 80.0%~99.0%, respectively, with the corresponding degree of precision (n=6) of 1.7%~7.3%, 1.3%~9.1% and 0.7%~4.6%. This method is simple, fast and with good sensitivity, recovery and precision, which is suitable for the determination of biogenic amines in Larimichthys polyactis.